Oral cavity status in menopausal and postmenopausal women - I.P. Mazur; V.A. Habal; M.S. Drohomyretska; K.M. Lykhota (Репродуктивная эндокринология, 2021)
The purpose of this review was to analyze and summarize the available literature data on changes of oral tissues in menopausal/postmenopausal women. We searched for the relevant references in Pubmed database using appropriate key words. We had revealed about 3,500 references on these topics and analyzed the most relevant. Postmenopausal women have an increased risk of the decrease of bone mineral density due to estrogen deficiency. Estrogens induce osteoclast apoptosis and intensity of this protective mechanism decreases after the cessation of menstruation. Most cross-sectional radiographic studies have confirmed an association between age-related osteoporosis and decreased alveolar bone height. It has been established that postmenopausal women with generalized chronic periodontitis are characterized by severe destruction of the periodontium, which progresses in parallel to a decrease in bone mineral density. Sex hormones maintaining bone integrity and strength, involved in regulating the proliferation, differentiation, and growth of keratinocytes and fibroblasts of the gums. The effect of low estrogen levels on keratinization of the gum epithelium and decreased salivation can lead to menopausal gingivostomatitis. Estrogen deficiency also adversely affects the microenvironment of gingival sulcus, including the composition and circulation of crevicular fluid. Postmenopausal women have lower salivary pH and lower salivation, which is associated with deterioration of periodontal tissues. In addition, the postmenopausal period is characterized by the changes in the microbial composition of the oral cavity, IgG decreases in the crevicular fluid and prooxidant changes of saliva. Conclusions. The oral cavity status in menopausal and postmenopausal women undergoes significant changes: a decrease in bone mineral density, dryness of mucous membranes, microbiome changes, and activation of oxidative and immune processes. These changes necessitate regular examinations, timely treatment and application of all measures of preventive dentistry. There is also a need for randomized clinical trials and create standardized guidelines for the management of postmenopausal patients with periodontal disease.